دور الإعلام في نشر العقيدة الإسلامية: التلفاز أنموذجا - الدوسري، مشتاق عماد عبدالعزيز (جامعة الأنبار - كلية العلوم الإسلامية, 2014)
يمثل الإعلام الإسلامي جسرا له أهميته البالغة في تواصل البشر، وتنبع هذه الأهمية من الدين الإسلامي نفسه، فهو دين دعوة، ودين إعلام، وما الإعلام الإسلامي إلا الوجه المعاصر للدعوة الإسلامية، وما الفرق بينهما إلا حداثة كلمة الإعلام، وعراقة كلمة الدعوة، ولأهمية الإعلام أطلق عليه خبراء الإعلام أنه (رسالة) بكل ما تعني هذه الكلمة، وهذه الرسالة ضرورة إنسانية صاحبت الإنسان من أول وجوده في الحياة الدنيا، قال تعالى: (قَالَ يَا آَدَمُ أَنْبِئْهُمْ بِأَسْمَائِهِمْ) ( ). فالإنباء هو مفهوم الإعلام ومعناه، استمر مع الإنسان حتى ارسال الرسل والرسالات المتضمنة للحق والدلالة للبشرية بمختلف الوسائل الإعلامية والوسائل المتوفرة في كل زمان ومكان، فأصبح الإعلام ضرورة في حق الإنسان، لتوظيفه لنشر العقيدة الإسلامية، ولأهميته ومكانته السامية جعل من وظائف الأنبياء والمرسلين الإنباء، بل ما سمي النبي نبيأ إلا لإنبائه وتبليغه الشرائع للاخرين. وأما العقيدة الإسلامية فهي جوهر الدين وأساسه، فالتأثير فيها سلبا أو إيجابا هو أخطر التأثيرات على دين المسلم، ولما كان الإعلام من أقوى المؤثرات -إن لم يكن أقواها-في عصرنا هذا على حياة الناس العقائدية والفكرية والسلوكية، كان البحث في دور الإعلام من أهم ما ينبغي أن ينشغل يه الباحثون. ولا سيما التلفاز؛ لأنه يعد أقدر وسيلة إعلامية حديثة عرفها الإنسان في عصرنا الحاضر؛ لأنه يجمع بين الصورة والصوت، وبذلك يسيطر على حاستي البصر والسمع، وهما من أهم الحواس وأشدها اتصالا بما يجري في نفس الإنسان من أفكار ومشاعر، وهو ينقل إلى الناس الحدث وقت حدوثه، نقلا كاملا مباشرا بما فيه من معان وانفعالات، ووجوده عند أغلب الناس يؤكد مدى تأثيره عليهم، ويعتقد بعض خبراء الإعلام بأل التلفاز منهج تعليمي قائم بذاته، بل قال بعضهم إنه المنهج الأول قبل المدرسة،
ولقد نافس التلفاز الكتاب في نقل المعرفة، والخبرات المتنوعة، وتؤكد التجارب الدولية العربية أن البرامج التعليمية إذا أحسن إخراجها ستكون فعالة أكثر من قراءة الكتب، ومما لا يخفى على متابع دور الإعلام الإسلامي في التلفاز بتقديم برامج وجوب الإيمان بالأركان الستة، وبخاصة برامج الإيمان التي تقدمها قناة الرسالة، ومن قبلها قناة إقرأ، ولا ينكر دور باقي الفضائيات بتقديم برامج في الإعجاز العلمي التي تدلل على وجود الخالق، ووحدانيته، وركزت في بحثي على الركن الأول من أركان الإيمان؛ لأنه هو الأساس لجميع الأركان، اذ كلها ترجع إلى الإيمان بالله تعالى، ولا فائدة من الدعوة والإعلام الإسلامي إن لم تنطلق من الإيمان بالله تعالى، وبرز دور التلفاز في نشر هذا الركن من خلال تقديم برامج ودروس علمية تدلل على وجود الله تعالى، وتقديم برامج يبث من خلالها صفات الله تعالى التي تليق بجلاله واخترت في بحثي إبراز صفة واحدة باختصار، ألا وهي الوحدانية، وللأعلام دور بارز في نشر الوحدانية من خلال نقل الآذان خمسة أوقات في كل أنحاء العالم بواسطة مختلف القنوات الإسلامية والعربية، ونقل شعائر الحج، ونقل قراءة القران الكريم وتفسيره، وتقديم برامج يبث من خلالها شرح أسماء الله الحسنى، وبراز قدرة وعظمة الجبار في خلقه، بتضمين الدروس الشرعية أدلة علمية إعجازية، والبرامج في هذا المجال كثيرة، واخترت الكلام على بث إعجاز اسم واحد من أسماء الله الحسنى فقط؛ ألا وهو الخالق. وللتلفاز دورا بارزا في تعظيم قدرة الخالق عندما يقدم برامج في إعجاز خلق الإنسان، وبث التقارير العلمية التي تفصل عجائب عالم الحيوانات وغرائبها، وإتقان تكوينها، ودقة صنعها، وبداعة تصويرها، بكل أصنافها، سواء منها الطائر، والسابح، والماشي، والزاحف، المتقنة في أشكالها، وأوضاعها، وألوانها، وخواصها، وطبائعها، وطرق عيشها، وكبيرها، وصغيرها، ما يكاد يجعل من المستحيل على الملحد ان يستمر في الحاده والادعاء بان كل هذا انما حدث مصادفة وبغير قوة مدبرة، ولهذا فقد بدء بعض هؤلاء الملحدين يتراجعون عن الحادهم، وصار بعضهم يشك فيه. فالقنوات التلفزيونية اتاحت للمسلمين فرصة لم تتح لهم من قبل في وسائل الاعلام الأخرى، لتعريف الغربيين بالإسلام، وللرد على الشبهات التي تثار حوله، حتى أن كثيرا من الإباء والأمهات في الغرب صاروا يفرحون بإسلام أبنائهم وبناتهم، حين يرون التغيير الحسن الذي طرأ عليهم.
Islamic media represents a bridge is critical for continued human beings, and stem the importance of the Islamic religion itself, it is the religion of the invitation, and the religion of the media, and Islamic media, but the contemporary face of the Islamic call, what is the difference between them, but modern word media, and the nobility of the word the invitation, and the importance of the media launched by media experts that (message) with all the means of the word, and this message is a humanitarian necessity accompanied the man from the first presence in the life of the world, he says: (He said: O Adam Onbihm names) Valanaba is the concept of the media and its meaning, continued with human even send messengers and messages contained to the right and the significance of mankind in various media available and means in every time and place, bringing the media need in the human right to employment for the dissemination of the Islamic faith, and the importance and prestige of the High Mark of the functions of the prophets and messengers to reports, but the so-called prophet prophet only better about and notification laws to others. And the Islamic faith are the essence of religion and the basis, Valtather which positively or negatively is the most dangerous effects on the Muslim religion, and what was the media of the strongest influences, if not Oquaha- of our time on people's lives ideological, intellectual and behavioral research was in the role of the media of the most important should be busy Yeh researchers. Especially television; it is appreciate modern media outlet known to man in our time; because it combines image and sound, and thus controls the senses of sight, hearing, two of the most important senses and most contact with what is happening at the same rights of thoughts and feelings, which is transferred to the people time of the event happen, citing a full directly with its gloss and emotions, and his presence when most people confirms its impact on them, some media experts believe that television curriculum stand-alone, but some of them said that the curriculum first pre-school
and I've competed television writers in the transfer of knowledge, and diverse experiences , Arab and international experience shows that educational programs if the best out would be more effective than reading books, making no secret observer role of Islamic media in television offering must be faith programs six pillars, especially faith programs offered by the message channel, and before Read Channel, does not deny the role of the rest of the satellite channels offer programs in scientific miracles that demonstrate the existence of God, Oneness, and My research has focused on the first pillar of faith; it is the basis for all the corners, as are all due to faith in God, do not benefit from the Dawa Islamic media that did not originate from Faith in God, and emerged as the role of television in the publication of this corner through the provision of programs and lessons scientific demonstrate the existence of God, and to provide programs broadcast in which the attributes of God Almighty that befits His Majesty and choose in a research highlighting the recipe and one short, not a singularity, and the flags of a prominent role in deployment of oneness through the transfer ears five times in all over the world by various Islamic and Arabic channels, and the transfer of the rites of the pilgrimage, and the transfer of reading the Koran and its interpretation, and provide programs broadcast in which the names of Allah, and to highlight the ability and the greatness of the mighty in His creation, include legitimate lessons scientific evidence miraculous, and programs in this area are many, and I chose to speak on the broadcast Ijaz name of one of the names of Allah only; not a creator. For TV prominent role in maximizing the ability of the Creator when programs Akadim in the miracles of human creation, and dissemination of scientific reports that separates the wonders of the world of animals and Graúbha and mastery of composition, precision manufacturing, and Bdaah photographed, all brands, both of which bird, swimmer, and Walker, and creeping, beautifully crafted in forms and conditions, and colors, and their properties, and natures, and ways of life, and large, and small, what makes it nearly impossible for an atheist to continue in the acute and the claim that all of this but coincidentally happened without housekeeper force, but this was the start of some of these atheists are shying away from atheism, and became some of them doubt it. Valguenoat television gave Muslims a chance they did not have before in other media, the definition of Western Islam, and to respond to suspicions raised around it, so that a lot of parents in the West have become rejoice Islam of their sons and daughters, when they see the change Hassan that has occurred to them.
Keywords: وسائل الإعلام -- العقيدة الإسلامية -- نشر الإسلام -- التلفزيون -- الوعظ والإرشاد